Genome Wide Identification and Characterization of Apple bHLH Transcription Factors and Expression Analysis in Response to Drought and Salt Stress - Mao, Ke; Dong, Qinglong; Li, Chao; Liu, Changhai; Ma, Fengwang (Frontiers in Plant Science, 2017)
The bHLH (basic helix-loop-helix) transcription factor family is the second largest in plants. It occurs in all three eukaryotic kingdoms, and plays important roles in regulating growth and development. However, family members have not previously been studied in apple. Here, we identified 188 MdbHLH proteins in apple ‘Golden Delicious’ (Malus × domestica Borkh.), which could be classified into 18 groups. We also investigated the gene structures and 12 conserved motifs in these MdbHLHs. Coupled with expression analysis and protein interaction network prediction, we identified several genes that might be responsible for abiotic stress responses. This study provides insight and rich resources for subsequent investigations of such proteins in apple.